EXPONENTIAL FUNCTIONS (Web of Teachers: Inderscience Research, 2023)
This article delves into the realm of exponential functions, a fundamental concept in mathematics and science. Exponential functions play a pivotal role in various disciplines, from finance to biology, demonstrating their versatility and significance. The article provides a comprehensive overview, analyzing existing literature, exploring methodologies, presenting results, and offering insightful discussions on the implications and applications of exponential functions.